STUDY OF TEMPERATURE AND ROASTING TIME ON THE QUALITY OF COCOA POWDER - Kurnia Herlina Dewi; Meizul Zuki; Mulad Subagio (BPFP Faperta UNIB, 2012)
This study aims to determine the effect of temperature and roasting time the quality of cocoa powder by SNI, to determine the effect of roasting time (100oC and 115oC) for the quality of cocoa powder (physical, chemical, biological, and organoleptic) and to determine the effect of roasting time : 30, 60, 90 and 120 minutes of quality cocoa powder. Variables in this study to determine the quality of cocoa powder consists only of fat content, moisture content, pH, microbial contamination is the number of colonies of bacteria, fungi, Escherichia coli, refinement, and organoleptic properties of the cocoa powder. Results obtained show the temperature effect and long penyangraian penyangraian nibs cocoa powder quality results as a whole meet the quality standards. Effect of roasting temperature to produce quality cocoa powder on the observation variables (pH, moisture content, fat content) and different organoleptic properties, whereas the level of tenderness, microbial contamination, cocoa powder is no different. The effect of roasting time to produce quality cocoa powder on the observation variables (pH, moisture content, fat content) and different organoleptic properties. The level of tenderness and microbial contamination non-significant.